TOWARD A RESOLUTION OF ANTINOMIES IN MAX SCHELER’S VALUE THEORY - Blosser, Philip (Philosophia reformata, 2012)
Two problems in Scheler’s thought are (1) his reason/feeling dualism, which artificially limits his classification of values, undermining the coherence of experience and its rational intelligibility; and (2) his restriction of moral value to a by-product of realizing non-moral values, which leads him to misidentify the value attaching to personal agency exclusively with moral value. To resolve these problems, I enlist Herman Dooyeweerd’s analysis of experiential aspects, analogical concepts, and subject-object relations, which illumine both Scheler’s insights and his oversights.